Determinan Pembiayaan UMKM pada BPR Syariah di Indonesia - Rifadli D. Kadir (Fakultas Ekonomi dan Bisnis Islam IIQ An Nur Yogyakarta, 2022)
This study aims to determine the effect of NPF (Non-Performing Financing), Inflation, and Company Size (Size) on MSME financing at Islamic BPRs in Indonesia, using time series data during January 2010 to December 2020 at Islamic People's Financing Banks (BPRS). issued by the Financial Services Authority (OJK). The method of analysis chosen for the purposes of data analysis uses the OLS (ordinary least square) estimation method using an error correction model (ECM). The results of this study indicate that the variable Inflation and Firm Size have a significant long-term effect, while the NPF variable has no significant effect. While the three variables do not have a significant short-term effect on MSME financing at Sharia BPRs in Indonesia.